Associative experiment and linguistic consciousness - Espekova Л.Ә.; Akhmetova М.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article highlights the role of the associative experiment in studying ethnic consciousness within the framework of modern anthropocentric paradigms. It is recognized as a method actively used in the comprehensive study of linguistic consciousness. Speaking about the problem of language and ethnicity, we will talk about its peculiarity in the cognition of the linguistic picture of the world. Taking ethnographisms as an object of study is an important factor in recognizing national and cultural characteristics. During the experiment, ten stimulus words from semantic groups of ethnographisms related to time, household items, distance and crafts were considered. During it, several groups of reaction words were identified, and their percentage indicators were differentiated. Based on the analysis, quantitative and qualitative characteristics of reaction words used as a feature and having an evaluative nature, forming one semantic field with stimulus words, were analysed. The collected materials show that the consciousness of Kazakh youth retains information formed in the traditions and way of life of the people. This allows them to recognize the model of the world, the conceptual picture of the world, and the national and cognitive features characteristic of society.